Relative serum amyloid A (SAA) values: the influence of SAA1 genotypes and corticosteroid treatment in Japanese patients with rheumatoid arthritis - Yamada, T (2001)
OBJECTIVES—(1) To determine whether serum concentration of serum amyloid A (SAA) protein is influenced by the SAA1 allele in Japanese patients with rheumatoid arthritis (RA) as previously shown in a healthy control group; and (2) to analyse what factors, based on such an allelic bias, influence the relative SAA values of those patients. METHODS—SAA and C reactive protein (CRP) concentrations together with SAA1 genotypes were determined in 316 Japanese patients with RA. The relative SAA values were evaluated as an SAA/CRP ratio. RESULTS—Comparison of the three SAA1 homozygote groups showed that the SAA/CRP ratio was highest in the 1.5/1.5 group (mean 9.0, p<0.01 v the other two homozygote groups) followed by the 1.3/1.3 group (mean 7.2, NS v the 1.1/1.1 group) and the 1.1/1.1 group (mean 4.0). The SAA/CRP ratio was significantly higher in patients receiving corticosteroids regardless of the presence of allele 1.5. No clear differences in the ratio between patients with or without amyloidosis were found. CONCLUSION—The SAA1.5 allele and corticosteroid treatment had a positive influence on SAA concentrations in serum. These findings are important when evaluating SAA concentration in inflammatory diseases and when considering the cause or treatment of amyloidosis.